Model Pemasaran Digital Operator Seluler Digital Indonesia ByU - Daniel Susilo; Maria Tiara (Journal of Management and Bussines (JOMB), 2023)
This research aims to analyze the digital marketing model of the Indonesian Digital Cellular Operator BYU which is the backbone of the profession in Indonesia and is available in various sectors or industries. ByU is one of the companies that is able to combine two spectrums in their digital marketing through the official Instagram account @byu.id. Through their Instagram account, they introduced a marketing model where the color palette determines cultural diversity and uses slang such as friendzone to combine it. Keywords: ByU, Digital Marketing, ISP, Internet, Krippendorf